A Survey of Diabetes Mellitus in a Sample of Children below 15 Years Attending Child Welfare Hospital - Sulaf A. Hussain (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: Determine the age and gender distribution of children who experience diabetes mellitus (DM) underthe age of 15 years and the presence of some associated factors that might be a predisposing factor for thedisease including obesity.Methodology: A cross-sectional study was conducted at diabetic clinic in Children Welfare Teaching Hospitalin Baghdad City during 2006. The study sample included diabetic children less than 15 years of age. Data weretaken from the patients' record and by direct interview with the patients' parents. Information includeddemographic data, as well as past history of the patient and his/her family relative to diabetes and other immunediseases.Results: Data analysis showed that there was an equal distribution of patients among the three age groups (I-5,6-10-, and 11-15 years) in a rate of 33% for each. Females had higher incidence rate (660/o) than males. Onset ofthe disease was mostly at age group I-3 years (32%) followed by age group 4-6 years (30%). IIistory of viralillness was present in 24% of patients and a positive family history of DM was found in 23% of them, and afamily history of autoimmune disease was positive in 13% of cases. Body weight at the first visit to the clinicwas mainly below the 50th percentile (42% within the 25th percentile) and only 4% of patients had a bodyweight within the 75th percentile.Recommendations: Health education about the disease and provision of health centers those are easilyaccessible for early diagnosis and treatment and uninerrupted insulin supply.